2016
DOI: 10.1039/c6sm00537c
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the twist-bend nematic phase: the characterisation of 1-(4-cyanobiphenyl-4′-yloxy)-6-(4-cyanobiphenyl-4′-yl)hexane (CB6OCB) and comparison with CB7CB

Abstract: The synthesis and characterisation of the nonsymmetric liquid crystal dimer, 1-(4-cyanobiphenyl-4'-yloxy)-6-(4-cyanobiphenyl-4'-yl)hexane (CB6OCB) is reported. An enantiotropic nematic (N)-twist-bend nematic (NTB) phase transition is observed at 109 °C and a nematic-isotropic phase transition at 153 °C. The NTB phase assignment has been confirmed using polarised light microscopy, freeze fracture transmission electron microscopy (FFTEM), (2)H-NMR spectroscopy, and X-ray diffraction. The effective molecular leng… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
129
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 188 publications
(160 citation statements)
references
References 54 publications
15
129
0
Order By: Relevance
“…Paterson et al. reported 1‐(4‐cyanobiphenyl‐4′‐yloxy)‐6‐(4‐cyanobiphenyl‐4′‐yl)hexane (CB6OCB—compound 6 in this work), finding that replacing one of the two methylene groups adjacent to the 4‐cyanobiphenyl mesogenic unit in CB7CB confers a modest increase in the N TB –N transition temperature, T NTB–N 46. Positioning a single ether link in the centre of CB7CB (to give an isomer of 6 /CB6OCB) lead to the finding that T NTB‐N drops dramatically relative to both parent materials.…”
Section: Introductionmentioning
confidence: 67%
“…Paterson et al. reported 1‐(4‐cyanobiphenyl‐4′‐yloxy)‐6‐(4‐cyanobiphenyl‐4′‐yl)hexane (CB6OCB—compound 6 in this work), finding that replacing one of the two methylene groups adjacent to the 4‐cyanobiphenyl mesogenic unit in CB7CB confers a modest increase in the N TB –N transition temperature, T NTB–N 46. Positioning a single ether link in the centre of CB7CB (to give an isomer of 6 /CB6OCB) lead to the finding that T NTB‐N drops dramatically relative to both parent materials.…”
Section: Introductionmentioning
confidence: 67%
“…It is also important to note that the organisation is only dependent on the bent architectures of the molecules and not to their conformational structures. Moreover, with any twisted organisation there is the possibility of two twists at right angles to one another, and in the case of the pitch length for the principal helical structure, for the materials investigated the results are all very similar, and in the 8-9 nm range, no matter what the details of the molecular aspect ratios are or the electrostatic properties [10,[18][19][20][21]. Overall, the results indicate that molecular topology determines the twist-bend phase stability and the pitch length.…”
mentioning
confidence: 97%
“…they occur below the melting point. Values for CB6OCB were taken from a forthcoming paper by Archbold et al [41]; however, these values are only marginally different to those reported by Paterson et al [33]. a If rapidly cooled, a monotropic, unidentified smectic phase (SmY) is observed at roughly 25°C for i14; however, the sample crystallises before this point during DSC study.…”
Section: Discussionmentioning
confidence: 85%
“…It has been observed that as the number of ether linkages increases, the scaled N TB transition temperature (T NTB-N /T N-Iso ) decreases irrespective of the actual values of T NTB-N . We therefore opted to reduce the number of ether-linking groups and prepare materials that can be thought of, in crude terms, as oligomeric analogues of CB6OCB, reported by Paterson et al [33], with our synthetic approach outlined in Scheme 3. We hypothesised that the reduction in the number of ether linkages would increase the scaled N TB transition temperature and therefore afford further examples of oligomeric twist-bend nematogens.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation